Effect of Pretreatment and Substrate Ratios in Biorefinery Employing Co-digestion of Plant Biomass and Poultry Waste - Shah, Fayyaz Ali; Rashid, Naim; Mahmood, Qaisar; Ali, Arshad (Frontiers in Energy Research, 2019)
The current study investigated the optimization of biogas generation during co-digestion of various plant biomasses with poultry waste at different ratios and pretreatment of plant biomass. The biochemical tests were executed at 35°C in a thermostat. Water hyacinth was found as the suitable substrate for mono and co-digestion due to high volatile solids (VS) and total soluble contents. However, poultry waste was appropriate only if it was co-digested with other biomasses. The experiments evaluating biogas generation at different ratios of plant biomasses and poultry waste demonstrated that water hyacinth and poultry (50:50) produced 262 mL g−1VS, giant reed and poultry (80:20) produced 235 mL g−1VSwhile maize and poultry (60:40) generated 193 mL g−1VS. However, the pretreating the plant biomass with either Fenton's or Fenton's plus ultrasonic had no effect on biogas generation. The volumes of biogas generated after various pretreatment were low as compared to condition without pretreatment. The codigestion can be classified as WH:P (50:50 > GR:P (80:20) > M:P (60:40). So, these ratios can be applied at decentralized scale for better waste management and biogas generation due to balanced C:N ratio of plant biomass and poultry manure. Co-digestion can also be applied at large scale with optimized ratio in Pakistan and other developing countries for biogas generation and waste management and reduce the methane emission through landfills.